POLARIZATION OBSERVABLES IN THE PROCESS (,np) ON 6Li NUCLEUS - Burkova, N. A.; Lennik, S. G. (Recent Contributions to Physics, 2009)
The asymmetry of the secondary particles in the process of two-nucleon photoemission 6Li( ,np)  α  has been calculated in multicluster dynamic model of 6Li nucleus with account of nucleonic and mesonicdegrees of freedom.
Keywords: dynamic model